Influence of Background Knowledge and Language Proficiency on Comprehension of Domain-Specific Texts by University Students - Justyna Kendik-Gut (Theory and Practice of Second Language Acquisition, 2019)
This paper presents the results of a quantitative study that explores two factors contributing to reading comprehension of domain specific texts, namely level of language proficiency and background knowledge. Overall, 32 students participated in the study by taking two custom-designed reading comprehension tests. The test scores were further  analyzed using SPSS statistical software. The results of statistical tests revealed the differences between study groups as well as the effects of compensation. More precisely, the most proficient group scored higher on almost all tests and completed the tests more quickly than the remaining groups. The statistical tools used to test the data showed that there are significant differences between all the groups in their performance on Proficiency Level Test and in timing. Hence, our hypothesis concerning the influence of background knowledge and language proficiency on reading comprehension of domain-specific texts has been confirmed. Finally, the paper discusses limitations of the study as well as implications for EFL teaching.